1988
DOI: 10.1021/bi00404a016
|View full text |Cite
|
Sign up to set email alerts
|

P10, A low molecular weight single-stranded nucleic acid-binding protein of murine leukemia retroviruses, shows stacking interactions of its single tryptophan residue with nucleotide bases

Abstract: Room temperature fluorescence and low-temperature phosphorescence studies of the association of p10, a basic low molecular weight single-stranded DNA binding protein isolated from murine leukemia viruses, point to the involvement of its single tryptophan residue in a close-range interaction with single-stranded polynucleotides. Optically detected triplet-state magnetic resonance (ODMR) techniques applied to the complex of p10 protein with the heavy atom derivatized polynucleotide poly(5-HgU) demonstrate the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 38 publications
2
5
2
Order By: Relevance
“…If tRNA was not included in the mixture, the fusion proteins migrated more slowly, indicating that these proteins were binding to the tRNA during the assay. This nonspecific binding is consistent with earlier work demonstrating that both gag polyproteins and nucleocapsid proteins bind nonspecifically to RNA in vitro (12,16,18,30,32,39,46,52,55,64).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…If tRNA was not included in the mixture, the fusion proteins migrated more slowly, indicating that these proteins were binding to the tRNA during the assay. This nonspecific binding is consistent with earlier work demonstrating that both gag polyproteins and nucleocapsid proteins bind nonspecifically to RNA in vitro (12,16,18,30,32,39,46,52,55,64).…”
Section: Resultssupporting
confidence: 91%
“…However, a recent report on Rous sarcoma virus has shown that efficient RNA encapsidation can occur when both Cys-His boxes have been deleted from the gag polyprotein (4). In addition, although in vitro binding studies have consistently demonstrated that NC proteins bind to single-stranded nucleic acids (12,16,18,30,32,39,52,55,64), most studies have failed to identify sequence-specific binding (16,39,52,55,64). Recently, a gel mobility shift assay has been used to measure in vitro binding of purified bovine leukemia virus (BLV) gag proteins to BLV genomic RNA segments; in this report, NC was shown to bind to all RNA segments analyzed, whereas MA was shown to bind only to the RNA segment containing the BLV packaging element T (33).…”
mentioning
confidence: 99%
“…Moreover, fluorescence studies showed an emission maximum at 350 nm, suggesting that the single tryptophan residue is probably solvent-exposed, in agreement with a previous report (29). Furthermore, the very low contribution of tyrosine fluorescence to the intrinsic protein fluorescence reflects an efficient energy transfer between Ty?'…”
Section: Discussionsupporting
confidence: 91%
“…To analyze the RNA binding and annealing activities of the modified NCplO proteins we have used MoMuLV RNA containing the primer binding site and the Psi element, that allow the specific annealing of the replication primer tRNA Pro and the selective dimerization and encapsidation of MuLV RNA, respectively (16,23,27). Previous in vitro studies have shown that cysteine modification of the zinc finger domain of NCplO does not affect its affinity for polyribonucleotides (6,40,41). However the biological relevance of these results remains questionable since non viral, synthetic RNAs have been used.…”
Section: Discussionmentioning
confidence: 99%